Nuevos datos sobre la distribución y la biología reproductiva de Canthon imitator Brown 1946 (Coleoptera: Scarabaeidae: Scarabaeinae) - Martinez M., Imelda; Escobar, Fernando; Almendarez, Sandra; Martínez, Ana Kory; González-Gómez, Lizbeth; González-Tokman, Daniel (Instituto de Ecología, A.C., 2019)
Canthon imitator Brown 1946 is registered for the first time in the Municipality of Papantla, Veracruz, Mexico. It is a roller, diurnal, coprophagous dung beetle, abundant in the collection site from May to July. The females have only the left ovary with one ovariola. A female oviposits a single egg every 4 to 5 days in a piriform nest ball. Males have two testicles with six spherical testicular follicles. The development to imago lasts approximately 30 days, as in the other Canthon species that have already been studied.